THE INFLUENCE OF ELECTRONIC SERVICE QUALITY ON THE SATISFACTION OF USERS OF THE SMOOTH APPLICATION AT THE CLASS I CORRECTIONAL INSTITUTION IN MALANG - Harsari, M Enrico Giralda; Pangestuti, Naniek (Universitas Nusa Cendana, 2025)
The aim of this research is to determine how influential the quality of electronic services is on public satisfaction among users of the 'smooth' application at the Class I Malang Correctional Facility. The researcher used a quantitative method with data collection techniques through questionnaires distributed to a sample of 129 active users of the 'smooth' application at the Class I Malang Correctional Facility. The data analysis used in this study includes simple regression analysis, significance testing, and determination testing, preceded by validity, reliability, and normality tests. The research results indicate that there is a significant influence of electronic service quality on public satisfaction. The research further reveals that electronic service quality affects public satisfaction by 61.2%, with the remaining 38.8% influenced by other variables not covered in this study. Keywords: Electronic Services; Public Satisfaction; Correctional Facility